Clean ebook - Junger, Alejandro (2012)
A Life-Changing Medical Breakthrough Clean is an M.D.'s program designed to be easily incorporated into our busy schedule while providing all the practical tools necessary to support and rejuvenate our bodies. The effect is transformative: nagging health problems will suddenly disappear, extra weight will drop away, and for the first time in our lives, we will experience what it truly means to feel healthy. Expanded Edition Includes: New Introduction • New Recipes • How to Become Clean for Life